ANALYSIS OF RISK FACTORS OF FILARIASIS IN KALEKE PUSKESMAS WORKING AREA AND BALUASE PUSKESMAS SIGI DISTRICT 2019 - Christine Christine Christine (Andalas University, Faculty of Public Health, 2021)
Sigi is a filariasis endemic district in Central Sulawesi. During 2013-2017, there were 81 cases, 11 people died, with the highest number of cases in Kaleke (16 cases) and Baluase (11 cases). Environmental factors affect the distribution and transmission. This study aimed to analyze the risk factors of filariasis in the work area of Kaleke and Baluase Health Center. This was an observational study with case-control design. The sample size was 54 people (18 cases and 36 controls). Research variables were 1) individual factors (gender and occupation); 2) behavioral factors (the habit of going out at night, the habit of hanging clothes in the house, the use of mosquito nets, the use of mosquito repellent); 3) physical environmental factors (use of wire mesh and presence of standing water). Factors related to filariasis were the habit of going out at night (p-value = 0.017), Odds Ratio=5.179,h means that people with the habit of going out at night are 5.176 more at risk of developing filariasis than those who do not. Suggestions for the community: 1) using mosquito repellent, long sleeve clothes and pants to reduce contact with mosquitoes; 2) keep the environment clean to prevent mosquito breeding and resting places.